2012
DOI: 10.4103/2230-8210.91204
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity and β-cell function in normoglycemic offspring of individuals with type 2 diabetes mellitus: Impact of line of inheritance

Abstract: Aims:The aim was to study the effect of family history of type 2 diabetes mellitus (T2DM) on insulin sensitivity and β-cell function in normoglycemic offspring.Material and Methods:Offspring of T2DM patients (cases) and individuals without family history of T2DM (controls) were the subjects for this cross-sectional study. All participants underwent 75 g OGTT and samples were collected for plasma insulin, C-peptide, and proinsulin at 0, 30, 60, and 120 minutes.Results:A total of 271 cases (age 22 ± 10 years; 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
4
12
1
Order By: Relevance
“…Offsprings of diabetic patients are known to have a high incidence of insulin resistance, beta secretory defects, altered glucose tolerance, and obesity. [27282930] All these were observed in the present cohort also. Around 40% of lean patients with gynecomastia had a family background of DM.…”
Section: Discussionsupporting
confidence: 82%
“…Offsprings of diabetic patients are known to have a high incidence of insulin resistance, beta secretory defects, altered glucose tolerance, and obesity. [27282930] All these were observed in the present cohort also. Around 40% of lean patients with gynecomastia had a family background of DM.…”
Section: Discussionsupporting
confidence: 82%
“…Results showed that the group with low M values represented approximately one-third of the high M value group, indicating that IR is present in approximately 25% of nonobese normal oral glucose tolerance individuals. Thus, some scholars suggested that hyperinsulinemia and IR exist prior to the occurrence of blood glucose abnormalities [ 1 , 2 ]. During the course of the disease, IR is the initiating factor in the majority of patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…IR widely exists in many pathophysiological states. Several researchers have suggested that IR already exists before blood glucose abnormalities in diabetic patients [ 1 , 2 ] and that hyperinsulinemia occurs before IGT shows several pathophysiological abnormalities. Therefore, several scholars have suggested that the T2DM process should be divided into the following three phases: hyperinsulinemia stage, prediabetes stage (IGT, IFG), and diabetes stage [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both, insulin resistance (IR) and β-cell dysfunction are critically important in the pathogenesis of the hyperglycemia of T2DM [1]. …”
Section: Introductionmentioning
confidence: 99%